Macrophages, PPARs, and Cancer. (22nd June 2008) - Van Ginderachter, Jo A.; Movahedi, Kiavash; Van den Bossche, Jan; De Baetselier, Patrick
Abstract : Mononuclear phagocytes often function as control switches of the immune system, securing the balance between pro- and anti-inflammatory reactions. For this purpose and depending on the activating stimuli, these cells can develop into different subsets: proinflammatory classically activated (M1) or anti-inflammatory alternatively activated (M2) macrophages. The expression of the nuclear peroxisome proliferator-activated receptors (PPARs) is regulated by M1- or M2-inducing stimuli, and these receptors are generally considered to counteract inflammatory M1 macrophages, while actively promoting M2 activation. This is of importance in a tumor context, where M1 are important initiators of inflammation-driven cancers. As a consequence, PPAR agonists are potentially usefull for inhibiting the early phases of tumorigenesis through their antagonistic effect on M1. In more established tumors, the macrophage phenotype is more diverse, making it more difficult to predict the outcome of PPAR agonism. Overall, in our view current knowledge provides a sound basis for the clinical evaluation of PPAR ligands as chemopreventive agents in chronic inflammation-associated cancer development, while cautioning against the unthoughtful application of these agents as cancer therapeutics.